P.M. Corner / Nur Ashiqyn Masuri … [et al.] - Masuri, Nur Ashiqyn; Mohamad Faisal, Anis Arlisha; Ab Razak, Nurdhia Ilyana Zulaikha; Amran, Siti Farah Syahirah (2022)
In this case study, the business was studied to analyze problems that relate the theory to a practical situation and help the entrepreneur to solve the problems. Therefore, doing this research could also inspire those who are interested in developing any business in the future. The business that I have chosen is P.M. Corner which was founded by Mr. Mohamad Faisal bin Zainal Abidin. The restaurant is located at Lorong Pandan Melaka, hence ‘P.M.’ stands for Pandan Mekar and the owner choose the word ‘Mekar’ so that the place he chooses to operate the business will always bloom. Their signature menu is “Roti Sarang Burung” which went viral for the past few months after Movement Control Order (MCO) in 2020. The mission of this restaurant is to attract more tourists and serves the best taste of food. The owner will ensure that every customer who comes will be satisfied with the taste of the food served. There is a lot of dishes that can be selected and mixed to complement everyone’s meal. While conducting this case study and from the interview with the owner of the business, there are a few problems that have been identified. The major problems that they are facing are, the business profit drops dramatically because of the pandemic Covid-19, food price management issues in a business’s system, and their competitor is selling at a cheaper price. As for the solution to the problem, the best recommendation is to be implemented.